INFOGRAFIS PANDEMI COVID-19 PADA MEDIA PERSS ONLINE DI INDONESIA - Handriyotopo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
ABSTRACT The phenomenon of infographics as a visual strategy attracts readers of digital newspapers to make them aware of the importance of protocols for the community as recommended by WHO and the government of the Republic of Indonesia in an effort to deal with the Covid-19 pandemic which is quite prevalent by online media perss. Through qualitative research methods on the phenomenon of infographic design with literature review of its constituent elements to find important infographic data in the online perss media. Literature research with literature studies as the object of covid-19 infographic material is in the local and national perss media which have been determined by positive sampling, the main ones are solopos.com, detik.com and kompas.com. The aim is to determine the visual elements of infographics and important messages of infographics in response to the Covid-19 pandemic related to health protocols during the new normal. The findings of this study are related to the form of infographics that are predominantly portrait or vertical where visual elements of color tend to be primary colors such as red, yellow, blue, and black to denote a pandemic-related color psychology. The visual metaphor tends to be iconic, such as the emphasis on header letters and the dominant copy (script) uses sanserif. Infographics always contain messages of equality in the meaning of complying with health protocols, such as the slogan of messages from 3 (three) M mothers, namely Wearing Masks, Washing Hands, and Maintaining Social Distancing which are the keywords for deciding the pandemic in all online perss. Keywords: Covid-19 infographics, aesthetics, visual rhetoric, online perss media